2020
DOI: 10.1038/s41598-020-74191-w
|View full text |Cite
|
Sign up to set email alerts
|

3D micro-organisation printing of mammalian cells to generate biological tissues

Abstract: Significant strides have been made in the development of in vitro systems for disease modelling. However, the requirement of microenvironment control has placed limitations on the generation of relevant models. Herein, we present a biological tissue printing approach that employs open-volume microfluidics to position individual cells in complex 2D and 3D patterns, as well as in single cell arrays. The variety of bioprinted cell types employed, including skin epithelial (HaCaT), skin cancer (A431), liver cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…For its printing technology, the Biopixlar uses a "microfluidic hydrodynamic confined flow" technology for building biological tissues from individual cells. [213][214][215] Specifically, the printer nozzle, in this case, is essentially a microfluidic device whose tip has one outflow channel in the center and two inflow ones at the sides (Fig. 7b).…”
Section: High-end Microfluidics-based Printersmentioning
confidence: 99%
See 1 more Smart Citation
“…For its printing technology, the Biopixlar uses a "microfluidic hydrodynamic confined flow" technology for building biological tissues from individual cells. [213][214][215] Specifically, the printer nozzle, in this case, is essentially a microfluidic device whose tip has one outflow channel in the center and two inflow ones at the sides (Fig. 7b).…”
Section: High-end Microfluidics-based Printersmentioning
confidence: 99%
“…As shown in a recent publication, 214 the Biopixlar was able to print up to three different cell types for fabricating 2D/3D complex tissue structures at a single-cell resolution. The printing process was shown to have maintained ~96-97% cell viability at 2 h postfabrication and a higher than 99% cell survivability after 24 h, when skin cancer (A431) and epithelial (HaCaT) cell types were used.…”
Section: High-end Microfluidics-based Printersmentioning
confidence: 99%
“…In this context, 3D culture systems have gained increasing interest as they are able to provide accurate models of organs or tissue physiology and associated disorders. However, they are not exempt from limitations, such as lack of nutrients and oxygen distribution, and accumulation of wastes into the core of 3D culture [ 236 , 238 , 239 ]. Diverse biomimetic engineered muscle constructs, such as scaffold or organoid cell culture, have demonstrated structural and functional characteristics similar to native muscle, mimicking the tissue complexity [ 240 , 241 , 242 ].…”
Section: Limitations In In Vitro and In Vivo Testing Of Novel Treamentioning
confidence: 99%
“…3D bioprinting has rapidly developed as a highly attractive technology for b metic implants that is able to support neuronal survival, counteract disease driving cesses and support functional repair following spinal cord injury [144]. Based on det information on the underlying pathophysiological processes and conditions of the pa 3D bioprinted implants may be designed to match patient-specific conditions [165] cent studies have demonstrated 3D bioprinted constructs that support neurite outgr from dorsal root ganglion neurons in vitro [166][167][168]. Dorsal root injury would be a u in vivo model for exploring these developments and their further translation to the in spinal cord.…”
Section: Bioprinting and Dorsal Root Injury Repairmentioning
confidence: 99%
“…Based on detailed information on the underlying pathophysiological processes and conditions of the patient, 3D bioprinted implants may be designed to match patient-specific conditions [ 165 ]. Recent studies have demonstrated 3D bioprinted constructs that support neurite outgrowth from dorsal root ganglion neurons in vitro [ 166 , 167 , 168 ]. Dorsal root injury would be a useful in vivo model for exploring these developments and their further translation to the injured spinal cord.…”
Section: Bridges For Dorsal Root Injury Repairmentioning
confidence: 99%